Migration-regime liberalization and social security : political-economy effect - Assaf Razîn; Edith Sand (Center for Economic Studies and ifo Institute (CESifo), 2009)
The pay-as-you-go social security system, which suffers from dwindling labor force, can benefit from immigrants with birth rates that exceed the native-born birth rates in the host country. Thus, a social security system provides effectively an incentive to liberalize migration policy. The paper examines a political- economy, inter-generational, mechanism through which the social security system influences voter attitudes in favor of more liberal immigration regime. We demonstrate that the Markov equilibrium, with social security, consists of more liberal migration policies, than the corresponding Markov equilibrium with no social security.
Keywords: F22; H55; J11; P16; 330; Migrationspolitik; Einwanderungsrecht; Deregulierung; Sozialversicherungsfinanzierung; Umlageverfahren; Einwanderung; Fruchtbarkeit; Public Choice; Theorie